Wayang Kulit Show, Layar Tancap (Traveling Cinema Show), and History of Pre-Cinema - Imanjaya, Ekky (Perkumpulan Program Studi Film dan Televisi Indonesia, 2024)
This article will investigate that Javanese and Balinese Wayang Kulit Performance should be considered a legitimate